КАЛЬЦИЕВЫЕ АМФИБОЛЫ ИЗ ПОРОД ПОЛОСЧАТОЙ ЖЕЛЕЗОРУДНОЙ ФОРМАЦИИ КОЛЬСКОГО ПОЛУОСТРОВА - Иванюк Г.Ю.; Пахомовский Я.А.; Базай А.В.; Яковенчук В.Н.; Горяинов П.М. (My University, 2005)
There were found magnesian and ferrous hornblendes, tschermakite and ferrotschermakite, magnesiosada-nagaite and pargasite, tremolite, actinolite and ferroactinolite among calcium amphiboles in rocks of banded iron-ore formation of Kola peninsula. Tremolite is the rock-forming mineral of hematite-magnetite quartzites and hydrothermal veins in biotite and aluminum gneisses; actinolite was detected in all types of ferrous quartzi-tes, in hornblende amphibolites, magnetite-diopside rocks and various hydrothermalites, ferroactinolite - in magnetite and sulfide-magnetite ferrous quartzites. Magnesian hornblende is the major mineral of hornblende amphibolites and various hydrothermalites, where tschermakite was also met; the ferrous hornblende is wide-spread secondary mineral of magnetite and sulfide-magnetite quartzites. In gabbroids, there are magnesian horn-blende, tschermakite, pargasite, ferrotschermakite and magnesiosadanagaite. Ore bodies have the characteristic zonality (from axial zone of their apical parts down to depth and to contact with biotite gneisses): hematite-mag-netite ferrous quartzites with talcum and tremolite - magnetite ferrous quartzites with actinolite and gruneri-te - sulfide-magnetite ferrous quartzites with grunerite, ferroactinolite and hedenbergite - skarnoids with acti-nolite, hornblende, biotite, epidope and garnets - magnetite-calcite-dolomite rocks with diopside and actinoli-te - nodular and two-mica gneisses. This zonality was developed, apparently, at first under action of an uprising deoxidized endogenic fluid at the progressive stage of metamorphism (formation of sulfide-magnetite and mag-netite zones), and then by means of reverse buffer reactions at the regressive stage (the reverse growth of hemati-te-magnetite and magnetite zones, formation of skarnoids and hydrothermal veins with actinolite and hornblen-de, alkaline autometasomatites with hornblende and aegirine).
Keywords: 549.643:553.31(=924.16)